Design of Matching and Decoupling Networks With Radiation Pattern Control for Two-Element Antenna Arrays - Son Vu; Hung Luyen (IEEE Open Journal of Antennas and Propagation)
We present an analytical approach for designing a matching and decoupling network (MDN) with radiation pattern control feature for two-element arrays. The antenna radiation pattern can be synthesized by formulating the S-matrix of the MDN to provide the desired excitation signals to the two antenna elements. Short transmission lines connecting reactive elements in the circuit are modeled as pi networks that are taken into account to calculate lumped element values. Through sensitivity analysis, we identified MDN solutions that are stable over tolerances in capacitance/inductance values of lumped components used to implement the MDN. To showcase the radiation pattern control capability, we developed two MDN versions that excite two distinct radiation patterns at 700 MHz for a two-element monopole array with an element spacing of 5 cm. S-parameters and radiation-pattern measurement results for both MDN-equipped antenna array prototypes align well with corresponding simulation results. The measured operating bandwidths (within which $|S_{11}|\lt -10$ dB, $|S_{22}|\lt -10$ dB, and $|S_{21}|\lt -20$ dB) were recorded as 6.2 MHz and 6 MHz for the two MDN versions. The total efficiency values were improved from 54% (for the coupled array) to 75% and 77% after incorporating the two MDN versions.